Blood Vessels and Vascular Niches in Bone Development and Physiological Remodeling - Hendriks, Michelle; Ramasamy, Saravana K. (Frontiers in Cell and Developmental Biology, 2020)
Recent advances in our understanding of blood vessels and vascular niches in bone convey their critical importance in regulating bone development and physiology. The contribution of blood vessels in bone functions and remodelling has recently gained enormous interest because of their therapeutic potential. The mammalian skeletal system performs multiple functions in the body to regulate growth, homeostasis and metabolism. Blood vessels provide support to various cell types in bone and maintain functional niches in the bone marrow microenvironment. Heterogeneity within blood vessels and niches indicate the importance of specialised vascular niches in regulating skeletal functions. In this review, we discuss physiology of bone vasculature and their specialised niches for haematopoietic stem cells and mesenchymal progenitor cells. We provide clinical and experimental information available on blood vessels during physiological bone remodelling.